Design of Cabinet Dryer for Pora-pora Fish (Mystacoleucus padangensis) - Mitrawijaya Tamba; Ainun Rohana; Achwil Putra Munir (Universitas Sumatera Utara, 2015)
The processing of food preservation to increase food (fish) storage abilityis interested to be known. One kind of the preservation is by drying. This research aimed to design, make, test and analyze cabinet dryer economyc value. Parameters observed were fish moisture contents, equipment capacity, and economic analysis. It was found from the research that fish moisture contents after dryin (dry base) was 38,69%. Capacity of the cabinet dryer was 0,92 kg/hour. Economic analysis, main cost to dry 1 kg fish was Rp. 6.285,4. Break event point (BEP) was 381,49 kg/year. Internal rate of return (IRR) was 59,77%. Keywords : Pora-pora fish (mystacoleucus padangensis), fish drying , cabinet dryer.